Evaluasi Penghawaan dan Pencahayaan Alami pada Desain Gedung Asrama Mahasiswa di Daerah Tropis - Siti Fatimah; Puteri Fitriaty; Andi Jiba Rifai Bassaleng (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Result of this study provides the recommendation of thermal and daylighting design strategies implementation in tropical-equatorial area, specifically student dormitory of Tadulako University in Palu Indonesia. This study employed literature, field, and mathematical study to analyses dormitory physical design, as well as thermal and lighting environment. Climatic variables were recorded both internal and external for 3 consecutive days. Result of the study indicated that the condition of Student Dormitory of Tadulako University needs to be improved. This study highlighted that opening area of 30%-50% from the floor area were needed. Furthermore, side-hung and jalousie window with light shelf were recommended for uniform daylighting and optimal air flow.